PrecHiMn-4—A thermodynamic database for high-Mn steels. (March 2017) - Hallstedt, Bengt; Khvan, Alexandra V.; Lindahl, Bonnie B.; Selleby, Malin; Liu, Shuhong
Abstract: This paper concerns a Calphad database that was developed to describe precipitation of cubic carbides and nitrides (V, Nb and Ti) in high manganese steels and to describe phase equilibria in high manganese steels with high aluminium content. The database has also been shown to be useful for calculations on medium manganese steels and low-density steels with varying aluminium additions. Thus the database covers a significant fraction of the steels that are termed advanced high strength steels (AHSS) of the second and third generation. A number of systems were assessed (or reassessed) for the database, namely Fe–Mn–Al, Fe–Mn–C, Fe–Nb, Mn–Nb, Fe–Mn–Nb, Fe–Nb–V, Fe–Nb–C, Mn–Nb–C, Fe–Mn–Nb–C, Nb–N, Fe–Mn–Nb–N. The remaining systems were taken from published assessments. The database covers the elements Fe, Mn, Al, Si, V, Nb, Ti, C and N. Highlights: Thermodynamic database with the elements Fe, Mn, Al, Si, V, Nb, Ti, C and N. Improved description of the Fe-Mn-Al-C system. Useful for high- and medium-Mn steels.